The practical application of a self-developed temperature stress testing machine in development of expansive concrete blended with calcium sulfoaluminate additives. (February 2023) - Ou, Guangfeng; Lin, Zhihai; Kishi, Toshiharu
Abstract: Early-age cracking of concrete is a complex problem related to temperature, restraint and curing conditions. Cracking sensitivity is hard to evaluate quantitatively and the use of expansive additives to mitigate cracking remains empirical in-situ. This study developed a Temperature Stress Testing Machine (TSTM) to evaluate early-age properties of concretes under varied engineering conditions. The general design of TSTM and the mathematical derivation of its working principle are provided. With the developed TSTM, early-age properties (free deformation, restrained stress, elastic modulus and early-age creep effect) of Calcium Sulfoaluminate (CSA) expansive concrete are tested comprehensively. Experimental results indicate that under high temperature condition, CSA concrete is not effective to compensate shrinkage, while the combination of CSA and lightweight aggregate resolves the problem. It offers us valuable insights on potential application of TSTM into mix design of crack-resistant concretes under complex engineering conditions.